Design, Development and Performance Evaluation of Fish Descaling Machine - Gaikwad, Nilesh N.; Ahmad, Tanbir; Yenge, Govind B.; Singh, Ajeet (Fishery Technology, 2017)
In fish post-harvest processing, one of the unit operations involved is removal of fish scales which is traditionally carried out by knife. The process is time consuming and cumbersome. This may also lead to injury to the person descaling the fishes. In this context, a hand held fish descaling machine has been designed and developed to increase the speed of descaling process, reduce the drudgery and improve the safety of operation. The fish descaling machine has important components such as descaling head, flexible shaft, safety shield, 1 hp motor, AC drive and a stand for fixing motor and A.C. drive. Four different types of innovative designs of descaling heads namely, diamond shaped, inverted V shaped, 13 slots and 26 slots were tested at different speeds for the capacity, efficiency, energy consumption and injuries inflicted. Performance of the machine was tested for two fish species using four descaling heads at 1440, 2000 and 2800 rpm. The diamond shaped descaling head with its unique design showed maximum descaling rate at 2800 rpm. The fish descaling machine reduced drudgery in descaling operation and also reduced the time required in descaling from 120 to 40 s for average 500 g fish vis a vis traditional hand tool in practice. There were no incidence of injuries reported to person descaling the fishes and also no skin damages to fishes while descaling. Average energy requirement was 0.25 kwh for the machine and an unskilled labour was required for operation. The machine is suitable for descaling of catla and silver carp fish species.